Analysis of Factors Affecting Self-Acceptance in Older Adult Living in Nursing Homes - Dessy Syahfitri Pohan; Elida Ulfiana; Ariina Qona'ah (Universitas Airlangga, 2021)
Introduction: Self-acceptance among older adult who lives in the nursing home tends to be poor. It is because they feel abandoned by their families and their inability to accept any changes that occur to them. Thus, older adults find it challenging to adapt to their new environment and cause various physical and psychological problems. The purpose of this study was to determine the factors of self-acceptance in older adults living in aged care based on an empirical study of the last ten years.Method: This study used a literature review design with electronic sources from 4 databases, namely Scopus, PubMed, Google Scholar, and Science Direct, which were published in the period 2010-2020. The keywords used are factors that influence or self-acceptance, older adults or elderly or aged, and nursing homes or nursing home.Results: Thirteen articles were analyzed in this study. Six research articles discuss social support as the most important factor of self-acceptance in older adults living in nursing homes. Other factors that influence self-acceptance in the older adult who lives in the nursing home include spirituality, religiosity, family support, and positive thinking.Conclusion: Social support is the essential factor in self-acceptance in older adults living in nursing homes.